Asymmetric Addition and Cycloaddition Reactions with Ylidene‐Five‐Membered Heterocycles. Issue 23 (26th October 2021) - Torán, Ricardo; Miguélez, Rubén; Sanz‐Marco, Amparo; Vila, Carlos; Pedro, José R.; Blay, Gonzalo
Abstract: Five‐membered heterocycles bearing an exocyclic double bond have been successfully used as substrates in asymmetric addition and cycloaddition reactions. Ylidene‐heterocycles are attractive substrates due to their high functionalization and the presence of an electrophilic conjugated exocyclic double bound that can participate in nucleophilic addition reactions as well as cycloaddition reactions, which may be triggered by the formation of aromatic intermediates or products in many cases. During the last decades, catalytic methodologies have been developed using ylidene‐heterocycles as substrates in order to synthesize useful optically active heterocyclic derivatives. 4‐Ylidene‐pyrazol‐5‐ones, isoxazolin‐5‐ones, 2, 3‐dioxopyrrolidines, rhodanines, oxazolidindiones, Erlenmeyer‐Ploch azlactones and 5‐ylidene‐thiazolones have been successfully used as substrates in asymmetric reactions. This review collects the powerful research in asymmetric addition and cycloaddition reactions where ylidene‐five‐membered heterocycles have been used. Abstract :